Penyuluhan Upaya Pencegahan Penularan Penyakit Covid-19 pada Anak Sekolah Dasar di Perumnas Kabupaten Simalungun - Kustoyo, Bambang; Taslima, Saufa; Purba, Yeni Trisna; Sihombing, Elida; Afrilia, Masraini (3031-8572, 2023)
The increase in Covid-19 cases continues daily, making it a global pandemic problem. Besides health effects, this pandemic also affects education conducted online, declining economy, and public psychology due to activity restrictions. This community service program focuses on health sector, providing education on clean and healthy lifestyle (PHBS) with direct practice as Covid-19 transmission prevention efforts. Prevention of spread and transmission is crucial in community life and activities. This program is expected to help break the transmission chain, especially during the new normal period. The target is residents, particularly children in Perumnas area, Simalungun Regency. This location was chosen based on observation showing minimal knowledge of clean and healthy lifestyle, especially among children. Therefore, this socialization program was conducted using language easily understood by them. The program included handwashing station installation, education on proper handwashing techniques, mask usage education, and distribution of vitamins and masks to residents